Addition of palm olein to lard‐supplemented diet indicates myocardial dysfunction and augments oxidative stress by authophagy‐lysosome pathway in rats. Issue 3 (14th December 2020) - Kurhaluk, Natalia; Bojková, Bianka; Kajo, Karol; Macháleková, Katarína; Kisková, Terézia
Abstract: This study evaluated a prolonged effect of palm oil addition to lard‐supplemented diet (PLD) on the oxidative status, lysosomal enzyme activities, markers of hepatotoxicity and basic lipid profile in female rats. Female Sprague‐Dawley rats received PLD (10% of total fat: 7.5% from palm oil and 2.5% from lard), and the control group received lard‐supplemented diet (2.5% fat) from 28 days of age for 14 weeks. Histopathological evaluation of the liver from animals fed the PLD showed slight steatosis and signs of mild chronic inflammation. Reduction of extramedullary hematopoiesis and an increased ratio of red/white pulp were observed in the spleen. PLD induced oxidative stress (evaluated in the liver, heart, spleen, muscle and kidney) evidenced by an increase in conjugated dienes and malondialdehyde in all tissues except the muscle; protein carbonyl derivatives were increased as well. The changes in the antioxidant enzyme activities in the evaluated tissues were ambiguous except for the prominent increase in the heart. Lysosomal enzyme activities showed a tendency to increase in the heart and kidney and to decrease in the muscle and spleen. The De Ritis ratio, which is a biomarker of hepatotoxicity, was higher in the heart from animals fed the PLD. The palm oil addition to the lard‐supplemented diet‐induced prominent oxidative stress, particularly in myocardial tissue with involvement of the authophagy‐lysosome pathway.